2023
DOI: 10.3390/bioengineering10080924
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Skin Reactions in Epicutaneous Patch Testing with Deep Learning: An Evaluation of Pre-Processing and Modality Performance

Abstract: Epicutaneous patch testing is a well-established diagnostic method for identifying substances that may cause Allergic Contact Dermatitis (ACD), a common skin condition caused by exposure to environmental allergens. While the patch test remains the gold standard for identifying allergens, it is prone to observer bias and consumes valuable human resources. Deep learning models can be employed to address this challenge. In this study, we collected a dataset of 1579 multi-modal skin images from 200 patients using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…In dermatology, image-based screening technologies are developed for the diagnosis and management of skin diseases [14,15,[35][36][37]. Recent studies have been conducted to assess the effectiveness of machine learning algorithms and convolutional neural networks models in precisely detecting and diagnosing ACD from patch test images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In dermatology, image-based screening technologies are developed for the diagnosis and management of skin diseases [14,15,[35][36][37]. Recent studies have been conducted to assess the effectiveness of machine learning algorithms and convolutional neural networks models in precisely detecting and diagnosing ACD from patch test images.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have been conducted to assess the effectiveness of machine learning algorithms and convolutional neural networks models in precisely detecting and diagnosing ACD from patch test images. In both studies, a cohort of 200 ACD patients was examined using a new medical device the Antera ® 3D camera (Miravex Limited, Ireland), while the acquired spectral 3D images were used to map chromophores' concentration (hemoglobin, and melanin) and skin parameters (texture, volume, folds, and fine lines) [15,35]. In the first study, the results indicated that the synergy of convolutional neural networks (CNNs) and machine learning algorithms can achieve a success rate of 85% in ACD detection, indicating a high level of correct diagnostic predictions [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, a dataset of 200 patients with ACD collected from Andreas Syggros Hospital in Athens, Greece, was used [14]. The dataset collection involved evaluating skin reactions to patch tests during three consecutive visits and capturing images using an Antera® 3D camera [14].…”
Section: A Datasetmentioning
confidence: 99%
“…In the present study, a dataset of 200 patients with ACD collected from Andreas Syggros Hospital in Athens, Greece, was used [14]. The dataset collection involved evaluating skin reactions to patch tests during three consecutive visits and capturing images using an Antera® 3D camera [14]. The patch testing procedure involved the exposure of the irritated region to a total of 30 allergen substances, involving dyes and chemicals such as Potassium Dichromate, Neomycin Sulphate and Paraphenylenediamine.…”
Section: A Datasetmentioning
confidence: 99%